Utility of reverse transcriptase - Multiplex ligation-dependant probe amplification (RT-MLPA) in the molecular classification of Diffuse Large B cell lymphoma (DLBCL) by cell-of-origin (COO) - Nicholas Dcunha; Dhananjayan Sakhti; Elanthendral Sigamani; Jagan Chandramohan; Anu Korula; Biju George; Marie Therese Manipadam; Rekha Pai (Wolters Kluwer Medknow Publications, 2023)
Classifying diffuse large B cell lymphomas, not otherwise specified (DLBCL, NOS), is based on their cell-of-origin (COO) which is included in the WHO classification (2016), is essential to characterize them better in context of prognostication. While gene expression profiling (GEP) considered the gold standard and more recently, the Nanostring-based approach, classify these tumors accurately, many laboratories with limited resources and instrumentation need an alternate approach that is reliable, inexpensive, and with a reasonable turnaround. The Reverse Transcriptase Multiplex Ligation Dependant Probe Amplification (RT-MLPA) to subtype DLBCL, NOS cases, as designed by CALYM group appears to provide a good alternative but needs to be validated in other centres. Therefore, this study evaluated DLBCL, NOS and compared the results of RT-MLPA to that obtained by immunohistochemistry using the Hans algorithm. Materials and Methods: Sixty-five DLBCL, NOS cases were included and the RT-MLPA was set up and standardized using probes that were designed by the CALYM study group. Briefly, RNA was extracted converted to cDNA and the 21-gene expression classifier that also included probes to detect MYD88 mutations and EBER mRNA was performed by MLPA. The results were analyzed by the open home grown software designed by the same group and compared to the results obtained by IHC. Results: Forty-four of the sixty-five cases provided concordant results (k = 0.35) and if the MYD88 results were to be used as a classifier the concordance would have improved from 67.7% to 82%. The 21 discordant cases were divided into five categories to provide a possible explanation for the discordance. Further 26% and 31% of the samples tested were positive for MYD88 mutations and EBER mRNA, respectively. The test had a turnaround of three days. Conclusion: The test provided moderate (67.7%) concordance when compared with IHC and perhaps would have provided higher concordance if compared with GEP. The test also has the advantage of providing information on the MYD88 and EBV infection status. It was found to be reliable, easy to perform and standardize, requiring only routine instruments available in most molecular laboratories. The RT-MLPA assay therefore provides an alternative for laboratories that would require subtyping of DLBCL, NOS cases in the absence of an access to GEP or other instrument intensive methods.